Policies for the development of the information society in the new member states - Claudio Feijóo; José Luis Gómez-Barroso; Edvins Karnitis; Sergio Ramos (Netcom)
Achieving the full incorporation of its citizens, territories and institutions to the new socioeconomic paradigm implied by the information society is a priority objective of the European Union. Achieving this objective is even more significant for the new members since it is probably the safest path in the mid to long term convergence process in which they are immersed. This article describes the evolution of the regional support plans for the progress of the information society launched in the Eastern and Central European countries. This analysis is repeated for the specificities of Latvia and the results obtained are subsequently analysed. The results are not quite satisfactory despite some progress achieved in recent years. However, Latvia has a clear strategic vision that connects future development with the existence of a series of productive processes where an efficient information management is the key element. The maintenance of this conviction could be the most solid value to move forward towards the effective integration of Latvia into the knowledge society.